Views of teachers regarding medical errors and patient safety education (Bangladesh Journal of Medical Education, 2017)
Background: Recently medical errors and patient safety have become increasingly important in the area of medical research Different international committees have long been demanding the early integration of education about errors and patient safety in undergraduate and graduate medical education .To integrate patient safety education into existing curriculum views of the teachers towards patient safety education is an important issue.Study objectives: To explore the views of the teachers regarding medical errors and patient safety education.Study design: Cross-sectional descriptive study.Place & period of the study: Selected medical colleges in Bangladesh, from July 2014 - June 2015.Study population: Study population was 32 clinical teachers.Sampling technique: Convenience sampling.Data collection instrument: Self administered structured questionnaireResults: The study revealed that the topic medical error and patient safety were mostly neglected in the curriculum. But the teachers had positive attitude towards patient safety education. All most all the teachers agreed that learning about patient safety before graduation would produce more effective doctors. They did not think that students had good understanding of patient issues (mean score 2.84). Teachers showed less confidence in error disclosure. Teachers (81.3%) had positive agreement that patients and relatives had important role in reducing error. Most of the respondents (93.7%) agreed that even the most experienced person can make errors.Bangladesh Journal of Medical Education Vol.7(1) 2016: 8-13